2017
DOI: 10.2217/cnc-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Academic outcomes and accommodations following adolescent sport-related concussion: a pilot study

Abstract: Aim:The purpose of this study was to examine academic achievement, absenteeism and school accommodations following adolescent sport-related concussion (SRC).Methods:A case-series was conducted among grade 8–12 students who suffered an SRC. The primary outcomes were change in pre- and post-concussion overall, core report card grade point average (GPA) and absenteeism due to concussion. The most helpful school accommodations were tabulated.Results:Pre- and post-concussion GPA was obtained from 33 students – 16 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…In a 2017 paper, Russel et al showed similar findings through a case series and reported no significant differences in GPA between pre-concussion and after concussion recovery. They also reported the median number of school days missed as 4 (IQR 2-8) [ 16 ]. In a 2019 paper, Russel et al conducted a prospective cohort study to once again show that no significant difference existed between pre-injury vs. post-injury overall or core grades amongst SRC students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2017 paper, Russel et al showed similar findings through a case series and reported no significant differences in GPA between pre-concussion and after concussion recovery. They also reported the median number of school days missed as 4 (IQR 2-8) [ 16 ]. In a 2019 paper, Russel et al conducted a prospective cohort study to once again show that no significant difference existed between pre-injury vs. post-injury overall or core grades amongst SRC students.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1, containing data pertaining to post-concussion academic performance, indicates three studies that utilized qualitative survey methods, four studies that assessed academic measures (GPA, report cards, and examination scores), and three studies that utilized published inventory or achievement testing tools (Post-Concussion Symptom Inventory, Pediatric Quality of Life Inventory Version 4.0, and Wide Range Achievement Test-III) [7,[10][11][12][13][14][15][16][17][18]. In regard to strength of evidence, 6 studies were classified as cross-sectional studies [6,7,11,12,18,19], 4 were cohort studies [10,15,20,21], 2 were case series [13,16], 1 was a prospective longitudinal study [14], 1 was a population-based retrospective before and after study [17]. "To determine if academic performance was lower in the academic calendar year that students sustain a concussion compared to the previous year when they did not sustain a concussion."…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to obtain report cards resulted in a reduction in the sample size used to examine the effects of SRC and SRF on school grades. However, this is a well-acknowledged challenge among studies examining academic outcomes in concussion and mild TBI and is difficult to overcome [24–26]. Despite this limitation, the mean change in grades between SRC and SRF student included in this study (<1%) is unlikely to be clinically meaningful or impact the student’s long term academic trajectory (i.e., graduation status, acceptance into post-secondary programs).…”
Section: Discussionmentioning
confidence: 97%
“…3 Youth with concussion can experience both short-term and long-term physical, emotional, cognitive and sleep-related symptoms. 4 5 Although individual symptoms can vary, 5 6 researchers have consistently identified negative effects on academics, [7][8][9][10] physiological functioning, [11][12][13][14] psychological well-being [15][16][17] and overall quality of life. 18 Best practices for managing concussion include education to promote appropriate knowledge, attitudes and behaviours among stakeholders (eg, students, parents, school staff and healthcare providers), 19 20 interventions to manage recovery 21 22 and protocols to support students returning to academics and school sports.…”
Section: Introductionmentioning
confidence: 99%